2013
DOI: 10.1002/clc.22163
|View full text |Cite
|
Sign up to set email alerts
|

What Do We Currently Know About Metabolic Syndrome and Atrial Fibrillation?

Abstract: Metabolic syndrome represents a cluster of atherogenic risk factors including hypertension, insulin resistance, obesity, and dyslipidemia. Considering that all of these risk factors could influence the development of atrial fibrillation, an association between atrial fibrillation and the metabolic syndrome has been suggested. Additionally, oxidative stress and inflammation have been involved in the pathogenesis of both metabolic syndrome and atrial fibrillation. The mechanisms that relate metabolic syndrome to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 86 publications
(116 reference statements)
0
33
0
Order By: Relevance
“…20,27 The presence of metabolic syndrome increases a patient's risk of developing AF and, for patients in AF, increases stroke risk ( Figure 1). …”
Section: Pathophysiology and Clinical Epidemiologymentioning
confidence: 98%
See 1 more Smart Citation
“…20,27 The presence of metabolic syndrome increases a patient's risk of developing AF and, for patients in AF, increases stroke risk ( Figure 1). …”
Section: Pathophysiology and Clinical Epidemiologymentioning
confidence: 98%
“…41,42 Mechanistically, insulin 8 resistance results in a pro-inflammatory environment within the myocardium, principally driven by elevations in levels of interleukin-1, C-reactive protein and reactive oxygen species. 27,43 This leads to myocardial remodelling, diastolic dysfunction and left atrial hypertrophy, changes collectively termed diabetic cardiomyopathy. 43,44 Together with associated autonomic neuropathy, these favour the development of AF.…”
Section: << Figure 1 >>mentioning
confidence: 99%
“…Generally, it has been related MS with higher risk of cardiovascular disease. More significantly, MS could increase the chance to suffer atrial fibrillation, an usual arrhythmia 42 . Factors involved would be oxidative stress, high blood pressure, low grade of inflammation, left atrial and ventricular remodeling and activation of renin-angitensinaldosterone system.…”
Section: Freely Available Online -Open Access Doi: 1014306/renhyd21mentioning
confidence: 99%
“…Tp-e/ QT and Tp-e/QTc ratios have been suggested as more accurate measures for the dispersion of ventricular repolarization compared to others parameters, and are independent from heart rate alterations [5][6]. Previous studies have consistently shown an association between metabolic syndrome X (MSX) and atrial arrhythmia such as atrial fibrillation (AF) [7][8][9]. However, there is not much data regarding the association between CSX and ventricular arrhythmia.…”
mentioning
confidence: 95%